2022
DOI: 10.3390/foods11070911
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Amaranth and Finger Millet as Ingredients in Wheat Dough and Bread for Increased Agro-Food Biodiversity

Abstract: Amaranth and finger millet are important food security crops in Africa but show poor bread making ability, even in composite wheat breads. Malting and steaming are promising approaches to improve composite bread quality, which have not been fully explored yet. Therefore, in this study, wheat was blended with native, steamed or malted finger millet or amaranth in the ratio of 70:30. Wheat/native amaranth (WHE-NAM) and wheat/malted amaranth (WHE-MAM) had longer dough development times and higher dough stabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
6
7
1
Order By: Relevance
“…The phytate content was considered the most critical antinutritional factor of the FM flours and ranged between 0.24 ± 0.07 and 0.79 ± 0.04 g/100 g dry matter (DM). These values are generally agreeing with, , or even lower than, , previous results for FM. Phytate was significantly higher in WM flours compared to the DH ones.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The phytate content was considered the most critical antinutritional factor of the FM flours and ranged between 0.24 ± 0.07 and 0.79 ± 0.04 g/100 g dry matter (DM). These values are generally agreeing with, , or even lower than, , previous results for FM. Phytate was significantly higher in WM flours compared to the DH ones.…”
Section: Resultssupporting
confidence: 90%
“…49 However, another preceding study also found no effect of MTD or STD on the protein content. 35 Furthermore, a reduced protein content due to HTT was reported by some authors, 45 while others found an increase. 14 Similar to the present study, Dharmaraj and Malleshi 10 found no impact of HTT on the protein content.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The reduction of gluten content as a result of SRB incorporation causes a lower dough strength and smaller capacity to resist deformation, results also observed in other studies when wheat flour was replaced with SRB [ 32 , 33 ]. The reduced deformation energy observed for doughs containing SRB was attributed to the lower glutenin content and dough strengths as previously reported in breads enriched in maize gluten feed, the by-product of the wet milling of maize grain [ 34 ] and in breads formulated with amaranth and finger millet [ 35 ].…”
Section: Resultssupporting
confidence: 68%
“…The characteristic high volume of wheat-based breads can be attributed to their gluten content, which allows the retention of the gas produced during fermentation and reflects the ability of bread dough to expand [ 39 ]. The replacement of wheat flour with SRB flour causes a gluten-dilution effect and the disruption of the gluten network by the reaction of fiber with gluten proteins [ 35 ], thus reducing the bread’s air-holding capacity and, consequently, the bread volume. Similarly, the height of bread loaves decreased as the SRB amount increased, from 3% in 10SRB bread to 28% in 25SRB formulation, due to the lower gluten content compared with the control, corroborating the results observed for bread volume.…”
Section: Resultsmentioning
confidence: 99%